Dinamika Peran Ganda Ibu Single Parent di Era Modern dalam Perspektif William J. Goode - Arif Sugitanata; Siti Aminah (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
This study explores the dynamics of the dual roles of single mothers in the modern era, encompassing both income-earning responsibilities and independent child-rearing. Grounded in William J. Goode’s dual role theory, this research analyzes how single mothers navigate psychological pressures and complex role conflicts arising from limited resources and time constraints. Using a qualitative-descriptive-analytical research design with a literature review method, this study finds that single mothers often experience “role overload” and “role conflict,” which negatively impact their emotional well-being as well as the social and emotional development of their children. These conditions are further exacerbated by social stigma and the lack of institutional support, which hinder their access to better economic and social opportunities. The implications of these findings highlight the urgency of more inclusive social interventions and public policies, such as childcare subsidies, skills training, and access to mental health services, to support single mothers in effectively fulfilling their roles. Additionally, campaigns to reduce social stigma against single mothers are essential in fostering a more supportive environment for their families. This study contributes to a deeper understanding of the challenges faced by single mothers and offers practical recommendations for policymakers to enhance family well-being in modern society.